Excel-based assistance in financial management of micro-enterprises in the catering industry - Ellen Theresia Sihotang; Riski Aprillia Nita; Kartika Marta Budiana (Universitas Muhammadiyah Malang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are productive economic activities that can be managed individually or through business entities. One of the micro businesses in the catering services sector in Surabaya is Bunda Tasty. These businesses face challenges in financial management that are not yet systematized. Record-keeping is still done manually using Excel and does not refer to the Accounting Standards for Entities without Significant Public Accountability (SAK-ETAP). The community service team, consisting of lectures from the Faculty of Economics and Business at Hayam Wuruk University (UHW) Perbanas, provides a solution in the form of financial management using the Excel for Accounting (EFA) application. This application is relatively simple and still utilizes Excel worksheets. The method used involves mentoring in the design and implementation of EFA along with its socialization. The mentoring activities, including the socialization of EFA, were conducted from March to August 2023. The community service activities consist of three main stages: preparation, implementation, and evaluation. A series of community service programs took place over approximately six months. Based on the evaluation, the activities were very successful and provided new knowledge for the partners. The partners can make decisions through systematized financial management. They have also implemented EFA in managing their business since September 2023.